Role of proximal tibial osteotomy in knee osteoarthritis - Mohammed, Farid; Ansari, Afzal; Kumar, Sanjiv; Khan, Yasir Ali; Verma, Vikas (International Journal of Research in Medical Sciences, 2017)
Background: Osteoarthritis is an inevitable consequence of aging and second only to cardiovascular diseases in producing severe chronic disability. Osteoarthritis is characterized by degenerative changes in articular cartilage of diarthrodial joints and subsequent new bone formation at the articular margin. It is the result of excessive aging that primarily produces an alteration in the ratio of total glycosaminoglycans to that of fiber content in the matrix. The aim was to evaluate the results of proximal tibial osteotomy in medial compartment osteoarthritis (OA) of knee in terms of relief of pain, range of movement, correction of deformity and functional outcome Methods: This prospective observational study was conducted on 24 patients in the age range 54 to 70 years at the department of orthopedics, Era’s Lucknow Medical College from July 2014 to May 2016. The femorotibial angle was assessed radiologically. A written informed consent was obtained. A closed wedge osteotomy was done followed by rehabilitation programme. Results: It was concluded that proximal tibial osteotomy is a satisfactory alternative to joint replacement surgery in osteoarthritis limited to medial compartment of the knee in developing countries like India. Conclusions: The study concluded that proximal tibial osteotomy is a satisfactory alternative to joint replacement surgery when the disease is restricted to medial compartment of the knee.